Variation of TTC Repeat Pattern In The Dna of Mycobacterium Leprae Isolates Obtained from Archeological Bones and Leprosy Patients From East Nusa Tenggara - Dinar Adriaty; Ratna Wahyuni; Iswahyudi Iswahyudi; Bimo Aksono; Toetik Koesbardiati; Indropo Agusni; Shinzo Izumi (Journal of Tropical Life Science, 2012)
The existence of leprosy or kusta or Morbus Hansen or Hansens disease has been known for years, including in Indonesia. Starting from the discovery of Mycobacterium leprae isolates from ancient bone (about 1.000 years B.C), the archaeological excavations results in East Nusa Tenggara, interesting questions arise about how the development of leprosy in eastern Indonesia is. Biology molecular study would become a powerful tool to investigate the presence of leprosy bacillary whether there are similarities between the genomes of M. leprae isolates in the primeval and the present. PCR examinations were performed on mandibular bone fragments from ancient human who lived 1000 years B.C. discovered in archaeological surveys on the island of Lembata and three leprosy patients from East Nusa Tenggara. The DNA extraction was performed using a kit from Qiagen products and its TTC repeating pattern was seen with the method of direct sequencing. It turned out that the TTC profile obtained from samples of archaeological was as many as 13 copies, while the repetition of TTC in three samples of leprosy patients were 15, 17 and 26 copies. The different number of TTC repetition shows the different isolates of M. leprae between in the ancient times and the present. Further studies are needed to verify the differences in the genome that occur, for example from the study of SNPs (single nucleotide polymorphisms).